1993
DOI: 10.1001/jama.269.17.2258
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter cold medications. A critical review of clinical trials between 1950 and 1991

Abstract: No good evidence has demonstrated the effectiveness of over-the-counter cold medications in preschool children. Further studies are required to clarify the role of these medications in children. Certain single over-the-counter medications and combinations have been shown to reduce cold symptoms in adolescents and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0
26

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 41 publications
1
80
0
26
Order By: Relevance
“…This is important, because antidiarrhoeals are not recommended and have a poor risk-benefit relation [19], but are frequently consumed in developing countries [1,2,11]. Something similar happened concerning common-cold drugs, whose efficacy is doubtful [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because antidiarrhoeals are not recommended and have a poor risk-benefit relation [19], but are frequently consumed in developing countries [1,2,11]. Something similar happened concerning common-cold drugs, whose efficacy is doubtful [20].…”
Section: Discussionmentioning
confidence: 99%
“…Os fármacos com ação antiinfecciosa e os medicamentos para tosse e resfriado são os mais utilizados em crianças 2,4,8,10,23,24 , principalmente em função do grande número de infecções respiratórias que elas apresentam 26,30 . No presente estudo, os problemas respiratórios foram responsáveis pelo maior contingente de morbidade entre as crianças estudadas.…”
Section: Discussionunclassified
“…A análise do conteúdo das prescrições permitiu sua classificação em adequadas ou inadequadas. Foram consideradas adequadas as prescrições em que a escolha, via de administração, intervalo de administração e tempo de uso do medicamento eram adequados para o tratamento do sintoma ou diagnóstico e/ou uso profilático, levando-se em conta eficá-cia, segurança e preço, de acordo com dados atuais de literatura 4,5,25,26,30,31,32,33 . Foram consideradas inadequadas as prescrições em que os medicamentos prescritos eram de indicação questionável por conterem substâncias de ação não comprovada, por apresentarem uma menor relação custo/benefício em relação a outros medicamentos igualmente eficazes ou quando se tratava de fármacos de uso não indicado para crianças ou fármacos contra-indicados para a faixa etária da criança.…”
Section: Variáveis De Estudo E Sua Operacionalizaçãounclassified
“…This is not the case, however, if the 2 most commonly used classes of OTC medications (those for coughs and colds and antipyretics) are examined. A series of systematic reviews have found that OTC cough mixtures are no more useful than placebo, [12][13][14][15] and the use of antipyretics in controlling fevers is of dubious value. 16 In fact, it appears that both doctors and parents have unrealistic expectations regarding the natural history of childhood coughs and colds, 17 and this is fertile ground for the advertising and sale of (inefficacious) OTC medications.…”
mentioning
confidence: 99%